The Difference In Neutrophil/Lymphocyte Ratio In Patients With Acute Appendicitis Without And With Perforation - Wismaya, IGP Wegen; Tahalele, Paul L; Rahayu, Titien (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: Acute appendicitis is an inflammation of the appendix vermiformis and is the most frequent cause of acute abdominal. Inflammation occurs due to microorganisms infection that enter the submucosal layer of the appendix and eventually involves all layers of the appendix wall. Acute inflammation can lead to an appendix lumen obstruction, resulting in venous blood engorgement and arterial stenosis. One of the acute appendicitis physiological response from the immune system is an increasing of neutrophils and decreasing of lymphocytes. The result of increasing neutrophils and decreasing lymphocyte are increasing the absolute ratio between neutrophils and lymphocytes Aim: To know the difference of neutrophil / lymphocyte ratio in patients with acute appendicitis without perforation and with perforation at Dr. M. Soewandhie District General Hospital Surabaya. Methods: This research is an analytical research with cross sectional study, with paired categorical analysis sampling method. Respondent of this research is 62 patients, which consist of 31 patients acute appendicitis without perforation and 31 patients acute appendicitis with perforation that fulfilled inclusion and exclusion criteria in January 2016-August 2017. This research was conducted at Dr. M. Soewandhie District General Hospital Surabaya from Saturday, August 19th, 2017 until Saturday, September 30th, 2017. Results: the difference of neutrophil / lymphocyte ratio in acute appendicitis patient without perofration and with perforation analyze by using Fisher?s Exact Test comparative statistic test, p value 0.000